Opportunities and Limitations of Crop Phenotyping in Southern European Countries - Costa, Joaquim Miguel; Marques da Silva, Jorge; Pinheiro, Carla; Barón, Matilde; Mylona, Photini; Centritto, Mauro; Haworth, Matthew; Loreto, Francesco; Uzilday, Baris; Turkan, Ismail; Oliveira, Maria Margarida (Frontiers in Plant Science, 2019)
The Mediterranean climate is characterised by hot dry summers and frequent droughts. Mediterranean crops are frequently subjected to high evapotranspiration demands, soil water deficits, high temperatures and photo-oxidative stress. These conditions will become more pronounced due to global warming which poses major challenges to sustainability of the agricultural sector in Mediterranean countries. Selection of crop varieties adapted to future climatic conditions and more tolerant of extreme climatic events is urgently required. Plant phenotyping is a crucial approach to address these challenges by utilising crop breeding, plant and agronomic sciences. High throughput plant phenotyping (HTPP) helps to monitor the performance of improved genotypes, and is one of the most effective strategies to improve the sustainability of agricultural production. In spite of the remarkable progress in basic knowledge and technology of plant phenotyping, there are still several practical, financial and political constraints to effective implementation of HTPP approaches in field and controlled conditions across the Mediterranean. The European panorama of phenotyping is heterogeneous and integration of phenotyping data across different scales and translation of “phytotron research” to the field, and from model species to crops remain major challenges. Moreover, solutions specifically tailored to Mediterranean agriculture (e.g., crops and environmental stresses) are in high demand, as the region is vulnerable to climate change and to desertification processes. The specific phenotyping requirements of Mediterranean crops have not yet been fully identified. Furthermore, the high cost of HTPP infrastructures is a major limiting factor, though the limited availability of skilled personnel may also impair its implementation in Mediterranean countries. We propose that the lack of suitable phenotyping infrastructure is hindering the development of new Mediterranean agricultural varieties and will affect negatively competitiveness of the agricultural sector. We provide an overview of the heterogeneous panorama of phenotyping within Mediterranean countries, describing the state-of-the-art of agricultural production, breeding initiatives and phenotyping capabilities in five countries: Italy, Greece, Portugal, Spain and Turkey. We characterise some of the main impediments for development of plant phenotyping in those countries and identify strategies to overcome barriers and maximise the benefits of phenotyping and modelling approaches to Mediterranean agriculture and related sustainability.